Selection of Internet of things (IOT) applications in education industry using the Best-Worst Multi-Criteria Decision-Making Method - M. Mohammadian; M. Sedighi; M. Serkani (Fanāvarī-i āmūzish, 2022)
Background and Objectives: Deploying IoT-based education can allow students to explore the environment using embedded sensors. They can access educational materials and other information at any time. Teachers can also use wearable devices and smartphones in the classroom to improve teaching and learning. Although new technologies such as smart schools, e-learning, e-learning content and smart classroom equipment have had a positive impact on the process of teaching and conveying concepts to learners, they have not been able to meet the challenges in this area well enough. Since the Internet of Things, in addition to using the mentioned technologies through technology convergence such as cloud computing, massive data, blockchain, smart phones, objects and classroom environment, etc. has a tremendous effect  on the education industry by creating  new teaching and learning methods, developing the systems of monitoring and control and improving the decisions through data analysis, it is argued that the IoT can empower the education sector to solve the problems and challenges it faces by providing practical solutions.Methods: This research is an applied research in terms of purpose and it is based on mixed methods research (qualitative- quantitative) considering how the data are collected.  At the beginning of the research, the Meta-synthesis method was used to identify the applications of the IoT in education. In this method, 4638 articles were found, and after being reviewed,  490 articles were extracted  among these  128 articles were used for the final analysis. Also, using the questionnaire as a tool to prioritize the Internet of things applications in education, the best-worst multi-criteria decision-making method  was  used.Findings: The findings showed that applications such as "Smart Campus" and "Student Health" have the highest priorities, respectively. Applications such as "Education (Teaching) and Learning", "Smart Class" and "Smart Tracking or Intelligent Transportation stsyem" were the next priorities.Conclusion: According to the findings, suggestions can be made to solve the problems of the education industry. In the field of application, with the help of IoT technology, there are problems such as the limitation of education to one place and time, wasting class time due to high density of people, lack of  intelligence and high maintenance costs of educational centers, lack of accurate monitoring of students' health and hygiene, and the inadequacy of educational facilities for the physically disabled reducing the lack of smartness of the transportation system. Education industry policymakers can also be advised to pay special attention to these areas, given that the areas of "smart health monitoring", "smart energy" and "security" are more important than other sub-applications and they should also pay attention to these special sections. Also, action should be taken for public education and extensive publicity in familiariing the society with smart products and IoT technology in order to increase user acceptance and create demand. Among the limitations of the research, the limited number of experts familiar with IoT technology in the country's education sector vcan be mentioned. It is suggested to examine the relationships between applications and sub-applications and their priority based on the feasibility and attractiveness of the indicators in the future research.